Transformasi Digital di Sektor Kesehatan Tinjauan Literatur tentang Penerapan Teknologi Informasi dalam Manajemen Pelayanan - Pristiya Maulaningrum; Siti Mujanah; Achmad Yanu Alif Fianto (Pusat Riset dan Inovasi Nasional, 2025)
Digital transformation in the health sector is a response to the demand for efficient, fast and accurate services. This study aims to systematically review the scientific literature related to the application of information technology in health service management in Indonesia. Through a review of ten scientific articles published in 2021-2024, it was found that digital technology has been applied in the form of web-based information systems, mobile applications, telemedicine, as well as information systems for non-communicable diseases and Posyandu for the elderly. These applications have contributed to improving operational efficiency, service accessibility, data-based decision-making, and community participation. However, a number of challenges are still faced, such as limited infrastructure, low digital literacy of health workers, not optimal protection of patient data, and not integrated systems between units. This study concludes that digital transformation demands technological readiness, human resources, and supportive policies. Recommendations are directed at strengthening infrastructure, increasing human resource capacity, drafting adaptive regulations, and developing integrated information systems.